KEANEKARAGAMAN MIKROALGA DITINJAU DARI FAKTOR FISIKA DAN KIMIA DI SUNGAI LOK ULO KABUPATEN KEBUMEN, JAWA TENGAH - Bagas Prakoso; Tititk Tri Wahyuni (Scripta Biologica, 2019)
Microalgae diversity research in the Lok Ulo River in Kebumen Regency, Central Java was conducted in September 2018. This study aimed to determine the diversity of microalgae in the Lok Ulo river. This research was conducted by field survey method. Determination of water sampling was chosen from 3 stations based on considerations to represent waters including: Station I (upstream part of the river), station II (middle part of the river) and station III (downstream part of the river). Each of the three water samples is taken. Water samples are taken to environmental laboratories for physical, chemical and biological analysis. The results showed that microalgae species found in the upstream, middle and downstream of the Lok Ulo river numbered 9 species, namely Oscillatoria sp., Cymbellahelvetica, Cymbellatumida, Cymbellanaviculiformis, Diatomaelongatum, Fragilaria sp, Synedraaccus, Synedraaffanis, Tabellaria sp. The relationship between TDS on microalgae diversity is shown through linear equations Y = 2.404-0.00014X. Based on these equations, TDS (X) in the Lok Ulo river is able to influence the diversity of microalgae with TDS is negative, every increase of 0.1 mg / l, TDS will reduce diversity by 0.00014 microalgae. The magnitude of the effect of TDS on the diversity of microalgae is indicated by the value of the correlation coefficient (r) of 0.972 with a significance of 0.000 there is a TDS relationship with diversity. The closeness of the relationship between TDS and the diversity of microalgae is indicated by the coefficient of determination (R2) of 94.5%. This means that the magnitude of the diversity of microalgae is influenced by TDS with closeness of 94.5.